Seasonal fluctuations of tissue mercury contents in the European shore crab Carcinus maenas from low and high contamination areas (Ria de Aveiro, Portugal) - Pereira, E.
The main objective was to study the seasonal variation of mercury concentrations in different tissues (muscle, hepatopancreas and gills) of Carcinus maenas from low and high Hg contaminated areas, a valuable resource in temperate estuaries and a possible pathway for human uptake. Individuals of two size classes (around 35 and 55 mm cephalothorax wide) were captured monthly between March 1999 and May 2000 in two areas of Ria de Aveiro: in the main navigation channel that connects the lagoon to the sea, and in the inner lagoon area heavily contaminated by mercury (maximum Hg in sediments of 5.4 μg g−1). Pronounced decreases in salinity and temperature and reduced food availability in winter seemed to be the responsible for the decline of the crab condition index (0.75–0.45) in larger individuals. Muscle and hepatopancreas exhibited higher mercury concentrations than gills, with concentrations in the contaminated site ranging from 0.03 to 0.63 μg g−1 and 0.02 to 0.34 μg g−1, respectively. Linear regressions between muscle and hepatopancreas (r = 0.94, p < 0.001) and muscle and gills (r = 0.97, p < 0.001) suggested a rapid redistribution of mercury inside the organism. During winter, a rapid elimination of mercury was found in the three analysed tissues followed by uptake. Larger crabs presented elimination rates from 18 to 34 ng g−1 per week, while the smaller crabs showed lower elimination rates (10–24 ng g−1 per week). The uptake was similar in both size classes (11–15 ng g−1 and 8.1–15 ng g−1 per week, respectively for large and small crabs). Our results suggest that C. maenas harvested in the contaminated areas must be considered with caution, since Hg concentrations were found to exceed the threshold concentration allowed for human consumption (0.5 μg g−1).